2021
DOI: 10.1038/s41598-021-96173-2
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of effects of incisor angle on production of sibilant /s/

Abstract: The effects of the inclination angle of the incisor on the speech production of the fricative consonant /s/ was investigated using an implicit compressible flow solver. The hierarchical structure grid was applied to reduce the grid generation time for the vocal tract geometry. The airflow and sound during the pronunciation of /s/ were simulated using the adaptively switched time stepping scheme, and the angle of the incisor in the vocal tract was changed from normal position up to 30°. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Studies demonstrated /s/ is the most frequently distorted when malocclusions or insertion of a prosthodontic restoration in the anterior region of the arch [21][22][23][24]. It also has been con rmed the central incisor position and inclination angle affect the production of the fricative consonant /s/ [11][12][13]. However, the impact of xed restoration on the changes of fricative acoustic features and speech movement behavior was not well illustrated [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated /s/ is the most frequently distorted when malocclusions or insertion of a prosthodontic restoration in the anterior region of the arch [21][22][23][24]. It also has been con rmed the central incisor position and inclination angle affect the production of the fricative consonant /s/ [11][12][13]. However, the impact of xed restoration on the changes of fricative acoustic features and speech movement behavior was not well illustrated [25].…”
Section: Discussionmentioning
confidence: 99%
“…Incisor overlap is a fundamental feature of anterior prosthetic restorations and cannot be simply complemented by aesthetics and occlusion standards as they are mostly achieved. It has been found that incisor overlap had a direct in uence on pronunciation [11][12][13], especially producing consonants like /s/ sound via obstructing and modifying the air ow. Therefore, it is necessary to clarify the relationship between overlaps of anterior restoration and pronunciation.…”
Section: Introductionmentioning
confidence: 99%
“…However, SLTS method is not suitable for aeroacoustic simulations even when the convergence criteria are satisfied because of the Newton linearization error of the term . Hence, adaptively switched time stepping scheme (ASTS) 24 , 25 was applied to maintain the accuracy in the aeroacoustic simulation at the same time reducing the computational cost.…”
Section: Methodsmentioning
confidence: 99%
“…This simple improvement yields critical benefits that will not cause errors in any types of geometry data, and is applicable to Cartesian grids. We have applied the variations of these methods to various industrial problems ( Bale et al, 2020 ; Cao et al, 2019 ; Jansson et al, 2019 ; Li et al, 2016 ; Lu et al, 2021 ; Onishi et al, 2018 ). For COVID-19 digital twins of societal situations, the optimal method was selected for one making it possible to automatically and robustly simulate complex dirty geometry, reducing the time required for preprocessing to about 10 min or less.…”
Section: Innovations Realizedmentioning
confidence: 99%